COVID-19 vaccination intention among healthcare workers in Vietnam - Giao Huynh (Asian Pacific Journal of Tropical Medicine, 2021)
Objective: To assess the acceptance of coronavirus disease (COVID-19) vaccine among healthcare workers at two general hospitals in Vietnam when it is available. Methods: A cross-sectional study was conducted using a convenience sampling from January to February 2021 among 410 healthcare workers at two general hospitals in Vietnam via a self-administered questionnaire. A multivariable regression analysis was performed to determine predictors of vaccine acceptance including the demographic factors, COVID-19 knowledge, and vaccine beliefs based on the domains of Health Belief Model. Results: Among 410 healthcare workers, 76.10% showed vaccination willingness. Predictors of acceptance were determined that the group reporting as “vaccine acceptance” was more likely to be positive towards the perceived susceptibility and severity of COVID-19 (OR 2.45; 95% CI 1.48-4.06, P<0.05), perceived benefits of vaccination, and cues to action (OR 4.36; 95% CI 2.35-8.09, and OR 5.49; 95% CI 2.84-10.61, respectively, all P<0.001), but less likely to have the perceived barriers to vaccination (OR 0.19; 95% CI 0.09-0.38; P<0.001) compared with the no acceptance group. Besides, people who had a good knowledge regarding the severity of illness were 3.37 times more likely to have identified as vaccine acceptance (OR 3.37; 95% CI 1.04-10.86, P<0.05). The demographic factors were also associated with willingness to receive the vaccine, with participants who were staff and received COVID-19 information from relatives were less likely to accept the vaccine over those who were doctors and not receiving information from relatives (OR 0.36; 95% CI 0.13-0.96, and OR 0.37; 95% CI 0.17-0.78, respectively, all P<0.05). Conclusions: A rate of willingness to get vaccinated against COVID-19 was relatively high with discrepancies between occupation, receiving information from relatives, knowledge toward the severity of illness, and the elements of Health Belief Model. The findings will provide information for the management authorities to develop relevant interventions to promote COVID-19 vaccination uptake.